Improvement of brain perfusion in patients with chronic brain ischemia at epidural spinal cord electrical stimulation - Zhao, Shu; Sufianova, Galina; Shapkin, Andrey; Mashkin, Andrey; Meshcheryakova, Svetlana; Han, Dayong (Frontiers in Surgery, 2022)
Objective Increasing life expectancy and aging of the population is accompanied by a steady increase in the number of elderly patients with chronic cerebral ischemia and age-related cognitive impairment associated with cerebral hypoperfusion and microangiopathy. The aim of this study was to identify long-term changes in cerebral blood flow (CBF) in patients with chronic cerebral ischemia at the epidural electrical stimulation of the spinal cord (SCS). Materials and methods Changes in cerebral blood flow were studied according to CT perfusion in 59 patients (aged 55–78 years) with vertebrogenic pain syndromes and chronic cerebral ischemia during epidural electrical stimulation of the spinal cord at the cervical (C3–C5) and lower thoracic (Th9–Th10) levels. Results In all patients, on the 5th day of trial SCS, an increase in cerebral blood flow by from 58.6 ± 1.13 ml/100 ml/min to 64.8 ± 1.21 ml/100 ml/min (p < 0.01) with stimulation at the Th9-Th10 level and from 58.8 ± 1.12 ml/100 ml/min to 68.2 ± 1.42 ml/100 ml/min (p < 0, 01) with stimulation at the C3-C5 level. These changes in brain perfusion were preserved during the follow-up examination 1 year after the implantation of chronic SCS system. The greatest increase in CBF was registered in the frontotemporal regions, subcortical structures and white matter of the brain. Changes in cerebral perfusion did not correlate with the degree of reduction in the severity of the accompanying pain syndrome. The change in CBF in the control group (32 patients) in all periods was not statistically significant. Conclusion Our results show that SCS is accompanied by a persistent improvement in brain perfusion, which may be potentially useful for developing methods for reducing age-related vascular disorders in the elderly.